Evaluation of Hazardous Chemicals with Material Safety Data Sheet and By-products of a Photoresist Used in the Semiconductor-Manufacturing Industry - Miyeon Jang; Chungsik Yoon; Jihoon Park; Ohhun Kwon (Safety and Health at Work, 2019)
Background: The photolithography process in the semiconductor industry uses various chemicals with little information on their constitution. This study aimed to identify the chemical constituents of photoresist (PR) products and their by-products and to compare these constituents with material safety data sheets (MSDSs) and analytical results. Methods: A total of 51 PRs with 48 MSDSs were collected. Analysis consisted of two parts: First, the constituents of the chemical products were identified and analyzed using MSDS data; second, for verification of the by-products of PR, volatile organic compounds were analyzed. The chemical constituents were categorized according to hazards. Results: Forty-five of 48 products contained trade secrets in amounts ranging from 1 to 65%. A total of 238 ingredients with multiple counting (35 ingredients without multiple counting) were identified in the MSDS data, and 48.7% of ingredients were labeled as trade secrets under the Korea Occupational Safety and Health Act. The concordance rate between the MSDS data and the analytical result was 41.7%. The by-product analysis identified 129 chemicals classified according to Chemical Abstracts Service No., with 17 chemicals that are carcinogenic, mutagenic, and reprotoxic substances. Formaldehyde was found to be released from 12 of 21 products that use novolak resin. Conclusion: We confirmed that several PRs contain carcinogens, and some were not specified in the toxicological information in the MSDS. Hazardous chemicals, including benzene and formaldehyde, are released from PRs products as by-products. Therefore, it is necessary to establish a systematic management system for chemical compounds and the working environment. Keywords: By-product, Material safety data sheet, Photoresist, Semiconductor, Trade secret